1989
DOI: 10.1121/1.397588
|View full text |Cite
|
Sign up to set email alerts
|

The acoustic surface wave above a complex impedance ground surface

Abstract: A surface wave like term arises in the analysis of spherical wave propagation above a complex impedance plane. Whether this wave is a true independently propagating surface wave, or a reaction to the incident air wave, has been the subject of discussion for a number of years. In this article, it is demonstrated that this term is a true surface wave that can exist independent of the body wave in air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…4 This wave does not exist at large numerical distances because Re sin p Ͻ 1. Raspet and Baird 15 have shown that Re sin p Ͻ 1 is not always true for semiinfinite porous layers described using the empirical laws of Delany and Bazley. 16 However, this condition has always been verified for semi-infinite porous layers when the causal equivalent densities and incompressibilities of the present work are used, and for the measurements described in the next section.…”
Section: Poles and Zeros Of The Reflection Coefficient For Semi-mentioning
confidence: 98%
“…4 This wave does not exist at large numerical distances because Re sin p Ͻ 1. Raspet and Baird 15 have shown that Re sin p Ͻ 1 is not always true for semiinfinite porous layers described using the empirical laws of Delany and Bazley. 16 However, this condition has always been verified for semi-infinite porous layers when the causal equivalent densities and incompressibilities of the present work are used, and for the measurements described in the next section.…”
Section: Poles and Zeros Of The Reflection Coefficient For Semi-mentioning
confidence: 98%
“…These authors used a form of the ray-tracing algorithm. Also notable are the modifications proposed by Raspet et al 257,258 , who expressed the solution as a residue series and normal mode solution for an upward and downward refracting atmosphere, respectively. This formulation is unlikely to provide any computational advantage.…”
Section: Far-field Noise Propagationmentioning
confidence: 99%
“…The theoretical basis for the generation of acoustic surface waves above an impedance plane has been investigated by many workers including Thomasson 2 who showed that if a surface has an impedance with an imaginary part much larger than the real part, an acoustic surface wave can be generated when the incident wave is at or near grazing incidence. Later, Raspet and Baird 3 demonstrated that such a surface wave is an independently propagating wave. Also, it was shown by Tolstoy 4,5 and Twersky 6 that acoustic surface waves can also be generated by rough surfaces.…”
Section: Introductionmentioning
confidence: 99%